6 minus radical din 20 totul sub radical
Răspunsuri la întrebare
Răspuns de
1
√(6-√20)=
=√[6+√(6²-20)]/2 -√[6-√(6²-20)]/2 =
=√[6+√(36-20)]/2 -√[6-√(36-20)]/2 =
=√(6+√16)/2 -√(6-√16)/2 =
=√(6+4)/2 -√(6-4)/2 =
=√10/2 -√2/2 =
=√5 -1
=√[6+√(6²-20)]/2 -√[6-√(6²-20)]/2 =
=√[6+√(36-20)]/2 -√[6-√(36-20)]/2 =
=√(6+√16)/2 -√(6-√16)/2 =
=√(6+4)/2 -√(6-4)/2 =
=√10/2 -√2/2 =
=√5 -1
dymalisnik:
1.236
Răspuns de
1
raspunsul=1.23606797749979
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă